Freestanding Silicene - Cahangirov, Seymur; Şahin, Hasan; Le Lay, Guy; Rubio, Angel (Springer Verlag, 2017)
Obtaining a freestanding 2D graphene flake is relatively easy because it has a naturally occurring 3D layered parent material, graphite, made up of graphene layers weakly bound to each other by van der Waals interaction. In fact, graphite is energetically more favorable than diamond (which is one of the most stable and hard materials on Earth) that is the sp3 hybridized allotrope of carbon. To prepare freestanding graphene, it is enough to come up with a smart procedure for isolating the weakly bound layers of graphite. The same is also true for other layered materials like hexagonal boron nitride, black phosphorus, metal dichalcogenides and oxides. Silicene, on the other hand, doesn’t have a naturally occurring 3D parent material since silicon atoms prefer sp3 hybridization over sp2 hybridization. This makes the synthesis of freestanding silicene very hard, if not impossible. However, it is possible to epitaxially grow silicene on metal substrates and make use of its intrinsic properties by transferring it to an insulating substrate (Tao et al. 2015). In this chapter, we focus on intrinsic properties of freestanding silicene in the absence of the metallic substrate.
Keywords: Nanosilicon; Silicene; 2D materials